Hierarchical Control of a Low Voltage DC Microgrid with Coordinated Power Management Strategies - Muchande, S.; Thale, S. (Engineering, Technology & Applied Science Research, 2022)
A microgrid consists of a cluster of renewable energy sources, energy storage elements, and loads. One of the main objectives of a microgrid is to provide reliable and high-quality power to the loads. Under normal operating conditions, this is achieved through suitable Power Management Strategy (PMS). However, under emergency conditions, such as the failure of any source, overloads, or faults, the PMS may not be able to retain the microgrid in operating conditions. Any emergency condition may demand a significant change in control and coordination between various subsystems of the microgrid to survive and continue the operation. This feature makes a microgrid "a fault resilient" system as visualized in its objectives. This paper proposes a novel Coordinated Power Management (CPM) strategy based on three-layer hierarchical control for an autonomous Low Voltage DC (LVDC) microgrid. The proposed CPM strategy ensures the continuation of the microgrid operation under normal and emergency conditions. An emergency control layer is established to extend the microgrid operation during an emergency condition. The performance of the proposed control scheme is validated through simulation and experimental results.